My life as a cartoonist - Tashjian, Janet; Tashjian, Jake, 1994- (New York : Henry Holt and Company, 2013)
Twelve-year-old Derek wants to train his pet monkey to help Umberto, a new student who uses a wheelchair, but Umberto would rather steal Derek's cartoon ideas
"Christy Ottaviano books."
Keywords: Cartoonists -- Juvenile fiction; Wheelchairs -- Juvenile fiction; Children with disabilities -- Juvenile fiction; Schools -- Juvenile fiction; Cartoonists -- Fiction; Wheelchairs -- Fiction; People with disabilities -- Fiction; Schools -- Fiction; Youths' art; Fiction